2021
DOI: 10.1080/23802359.2020.1871436
|View full text |Cite
|
Sign up to set email alerts
|

Complete chloroplast genome sequence of Procris crenata C.B.Rob (Urticaceae)

Abstract: The complete chloroplast (cp) genome of Procris crenata C.B.Rob was reported. The cp genome was 154,124 bp in length and contained two inverted repeats (IRs) of 25,626 bp, which were separated by large single-copy and small single-copy of 84,599 bp and 18,273 bp, respectively. The GC content was 36.5%. A total of 113 functional genes were encoded, comprising 79 protein-coding genes, 30 tRNA genes, and four rRNA genes. This is the first reported plastid genome in Procris … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
1
0
0
Order By: Relevance
“…Previous studies showed that the genera of Boehmeria and Debregeasia species were each closely clustered into one group (Wu et al. 2018 ; Fu and Zhang 2021 ), which was consistent with our study results of phylogenetic analysis. However, the phylogenetic analysis of Laportea genus has not been reportedyet, its the first time to make phylogenetic analysis for L. bulbifera species.…”
supporting
confidence: 93%
“…Previous studies showed that the genera of Boehmeria and Debregeasia species were each closely clustered into one group (Wu et al. 2018 ; Fu and Zhang 2021 ), which was consistent with our study results of phylogenetic analysis. However, the phylogenetic analysis of Laportea genus has not been reportedyet, its the first time to make phylogenetic analysis for L. bulbifera species.…”
supporting
confidence: 93%